2022
DOI: 10.1039/d2tc00698g
|View full text |Cite
|
Sign up to set email alerts
|

714 nm emission with 12.25% efficiency from iridium complexes with low iridium content by the strategy of rigid coordination core and amplifying shell

Abstract: Development of near-infrared (NIR)-emitting phosphorescent emitters are still urgent need for solution-processed organic light-emitting diodes (SP-OLEDs) with high efficiency and radiant emittance, low cost. Herein, we designed and synthesized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Therefore, deep red phosphorescent metal complexes with moderate emission efficiencies have been majorly limited to a few Ir(III) and Os(II) complexes with triplet metalto-ligand charge transfer ( 3 MLCT) excited states which have fast radiative decay rates owing to the strong spin-orbit coupling interactions. [4][5][6][7][8][9][10][11] Although the use of highly rigid porphyrin ligand to suppress nonradiative decay have also been explored for attaining deep red phosphorescence of square-planar Pt(II) and Pd(II) complexes, [12][13][14][15] the emitting states are usually extremely long-lived, which limit the maximum brightness, efficiency rolloff and operational stability for devices. These problems are also what the deep red thermally activated delayed fluorescence (TADF) molecules have been suffering from which are either weakly emissive or long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, deep red phosphorescent metal complexes with moderate emission efficiencies have been majorly limited to a few Ir(III) and Os(II) complexes with triplet metalto-ligand charge transfer ( 3 MLCT) excited states which have fast radiative decay rates owing to the strong spin-orbit coupling interactions. [4][5][6][7][8][9][10][11] Although the use of highly rigid porphyrin ligand to suppress nonradiative decay have also been explored for attaining deep red phosphorescence of square-planar Pt(II) and Pd(II) complexes, [12][13][14][15] the emitting states are usually extremely long-lived, which limit the maximum brightness, efficiency rolloff and operational stability for devices. These problems are also what the deep red thermally activated delayed fluorescence (TADF) molecules have been suffering from which are either weakly emissive or long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…35 In the past few years, our group reported a series of Pt(II) complexes based on C^N ligands. [36][37][38][39][40][41] The typical binuclear Pt(II) complex of (2niq) 2 Pt 2 (1-OXT) 2 with a butterfly geometry displayed an appealing EQE of 8.86% at 704 nm in the solution-processed PLEDs. 37 However, there are still serious challenges in getting highefficiency deep-red to NIR emission at high doping concentrations or current densities, even under longer luminescence wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that rigid C^N ligands bearing azaacenes indeed could suppress non-radiative processes and result in an improvement of device performance. [41][42][43][44][45] Moreover, the peripheral substituents in the C^N coordinated skeleton further play a vital role in maintaining sufficient solubility and finely tuning the optoelectronic properties. As a result, we shifted emission peaks from the deep-red (685 nm) to near-infrared region (852 nm) for iridium (III) complexes by delicate chemical structure modifications.…”
Section: Introductionmentioning
confidence: 99%